GAMBARAN POLA KONSUMSI MAKANAN PADA ANAK USIA 12-24 BULAN - Wiwit Radika; Riri Novayelinda; Hellena Deli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Children aged 12-24 years is the most important period in human life. The children's food consumption patterns should be considered because if nutrition during this period is less or more it will hinder the growth and development of children for the future. This study aims to identify food consumption patterns of children aged 12-24 months in Puskesmas Sidomulyo. This research is descriptive study with cross sectional approach. Sample in this study amounted to 79 respondents. Data were collected using a questionnaire which is modified from the Food Frequency Questionnary (FFQ). Respondents filled out a questionnaire for 7 days. The results showed that the characteristics of the majority of respondents aged 12-18 months were 71 respondents (89,9%), (54,4%) of the children in this study are male. Results showed that 62% of respondents consume a complete compotition of food per day that contains carbohydrates, protein, and fat, 82,3% of respondents have least three times meal time a day, 98,7% of respondents have can fulfill the amount of energy needed per day. This reseach suggest to public health centers staff and posyandu staff could giving a health education to parents.Keywords: children, people, patterns, food frequency questionnary (ffq)